Probing the furanose conformation in the 2 `-5 ` strand of isoDNA:RNA duplexes by freezing the nucleoside conformations - Erande, Namrata D.; Gunjal, Anita D.; Fernandes, Moneesha; Kumar, Vaijayanti A. (Chemical Communications, 2011)
Sugar conformations in the isoDNA strand of isoDNA : RNA duplexes are preferred S-type locked/frozen in contrast to N-type locked conformations preferred in DNA: RNA duplexes.